Propuesta de aplicación de buenas prácticas de manufactura en los procesos de higiene y manipulación de alimentos en el comedor universitario de la Universidad Estatal de Bolívar, año 2023 - Carrillo Bedón, Lililibeth Brigette (2023)
The objective of the research project was the elaboration of a manual of good manufacturing practices in the hygiene and food handling processes in the dining room of the State University of Bolívar, therefore this application process significantly affects food safety for consumers. students, teachers, workers and employees. The analytical and inductive method was used as a methodological background, together with a descriptive and exploratory investigation, the project had a mixed approach since qualitative and quantitative approaches were used. On the other hand, it was discovered that in the university canteen they are not applying the tools in the handling of food and in turn present a poor conservation of food hygiene due to the misuse of solid waste, generating contamination in the products that are offered and illnesses in diners. It should be noted that the good use of the manual of good manufacturing practices in hygiene and food handling processes is a driving force for correct food safety, for good hygiene procedures and quality products, therefore it is recommended that they need to maintain monitoring of sanitation procedures and control of raw materials. Keywords: good manufacturing practices, hygiene processes, food handling, food safety, quality, habits